2006
DOI: 10.1016/j.socscimed.2005.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies as predictors of psychosocial adaptation in a sample of elderly veterans with acquired lower limb amputations

Abstract: This study examines the contribution of demographic/amputation-related variables and coping strategies to the prediction of psychosocial adaptation in veterans with acquired lower limb amputations. Multiple indicators of the psychosocial adjustment of 796 individuals in the UK aged between 26-92 years with lower limb amputations were assessed. Hierarchical linear regressions were performed to investigate relationships between demographic/amputationrelated variables (i.e. age, time since amputation, amputation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
0
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 49 publications
6
91
0
7
Order By: Relevance
“…Moreover, they reported high levels of social support. Task-oriented coping strategies were previously associated with lower levels of anxious-depressive symptoms [5,37], and perceived social support has been found to predict a positive adjustment to amputation [38][39][40]. This study also considers different aspect of personality; although there is insufficient knowledge concerning the traits assessed by the EPQR-SF lie scale [36], the participants' high scores on this scale seem to reflect the practical way in which they coped with limb loss.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, they reported high levels of social support. Task-oriented coping strategies were previously associated with lower levels of anxious-depressive symptoms [5,37], and perceived social support has been found to predict a positive adjustment to amputation [38][39][40]. This study also considers different aspect of personality; although there is insufficient knowledge concerning the traits assessed by the EPQR-SF lie scale [36], the participants' high scores on this scale seem to reflect the practical way in which they coped with limb loss.…”
Section: Discussionmentioning
confidence: 92%
“…Investigation of the role of coping strategies in adjustment to lower limb amputation, consistent with the wider coping literature, suggests that active/task oriented strategies such as problem solving and perceiving control over the disability are conducive to positive psychosocial adjustment (e.g. 7,11,12). In contrast, emotion-focused and passive strategies such as cognitive disengagement, avoidance and catastrophizing have been associated with poor psychosocial outcomes 5 (7,12,13).…”
Section: Introductionmentioning
confidence: 83%
“…7,11,12). In contrast, emotion-focused and passive strategies such as cognitive disengagement, avoidance and catastrophizing have been associated with poor psychosocial outcomes 5 (7,12,13). For example, Livneh, Antonak & Gerhard (7) found that greater active problem solving was negatively associated with depression and internalised anger and positively associated with adjustment and acceptance of disability.…”
Section: Introductionmentioning
confidence: 99%
“…3 There is little consensus, however, regarding the prevalence of clinically significant emotional distress following limb amputation, either in the short or longer term. While some studies report elevated prevalences of clinically significant affective disorders among individuals with amputations compared with the general population, 4,5 others do not.…”
Section: Introductionmentioning
confidence: 99%